Adulthood personality correlates of childhood adversity - Carver, Charles S.; Johnson, Sheri L.; McCullough, Michael E.; Forster, Daniel E.; Joormann, Jutta (Frontiers in Psychology, 2014)
Objective: Childhood adversity has been linked to internalizing and externalizing disorders and personality disorders in adulthood. This study extends that research by examining several personality measures as correlates of childhood adversity. Method: In a college sample self-reports were collected of childhood adversity, several scales relating to personality, and current depression symptoms as a control variable. The personality-related scales were reduced to four latent variables, which we termed Anger/Aggression, Extrinsic focus, Agreeableness, and Engagement. Results: Controlling for concurrent depressive symptoms and gender, higher levels of reported childhood adversity related to lower Agreeableness and to higher Anger/Aggression and Extrinsic focus. Conclusions: Findings suggest that early adversity is linked to personality variables relevant to the building of social connection.